Designing an Information Technology Governance Roadmap for Prioritising Initiatives Based on the COBIT 2019 Framework and Mcfarlan Grid Risk-Value Analysis - Hendi Novianto Novianto; Raden Venantius Hari Ginardi (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
Digital transformation intensifies the strategic role of information technology (IT) governance in maintaining operational performance and competitive advantage. PT Perusahaan Gas Negara (PGN), a state-owned energy company, faces challenges in aligning IT investments with business priorities while managing escalating technological risks. This study integrates the COBIT 2019 framework with a value-risk prioritization approach using the McFarlan Strategic Grid to develop a structured improvement roadmap. A qualitative descriptive case study was conducted through observation, capability assessments, interviews, and literature reviews. Evaluation of fifteen priority COBIT processes yielded an average capability score of 3.67, reflecting a Defined/Established maturity level. The McFarlan analysis classified 28 consolidated initiatives into four priority clusters. The resulting roadmap supports strategic alignment, risk-sequenced execution, and executive decision-making.